2008
DOI: 10.2475/05.2008.01
|View full text |Cite
|
Sign up to set email alerts
|

From sea level to high elevation in 15 million years:Uplift history of the northern Tibetan Plateau margin in the Altun Shan

Abstract: Approximately 1300 m of Oligocene-Miocene clastic strata are exposed along the Miran River in the southeastern Tarim basin, where the adjacent Altun Shan form the topographic escarpment of the northern Tibetan Plateau. The sedimentary section is faulted against Proterozoic rocks of the Altun Shan in the footwall of the south-dipping, oblique reverse Northern Altyn Tagh fault. Oligocene-Lower Miocene strata consist of fine-grained rocks that record low-gradient depositional systems. Mid-Miocene and younger rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 26 publications
10
117
0
3
Order By: Relevance
“…The intensity contrast between the two episodes likely indicates that, during the first episode, the front of the proto-West Kunlun orogen at the edge of the plateau was further south from its present position, and it only propagated to its present position during the second episode. Our results therefore suggest that the northwestern edge of the Tibetan Plateau underwent two major episodes of propagation since B23 Myr: one at B23-12 Myr and the other since 5 Myr, leading to the region being uplifted from near sea-level 10 to the present height of 46,000 m (B5,000 m relative to the Tarim foreland basin). Such a two-episode uplift history is comparable to the two episodes of rapid cooling events recorded along the eastern margin of the Tibetan Plateau 3 .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The intensity contrast between the two episodes likely indicates that, during the first episode, the front of the proto-West Kunlun orogen at the edge of the plateau was further south from its present position, and it only propagated to its present position during the second episode. Our results therefore suggest that the northwestern edge of the Tibetan Plateau underwent two major episodes of propagation since B23 Myr: one at B23-12 Myr and the other since 5 Myr, leading to the region being uplifted from near sea-level 10 to the present height of 46,000 m (B5,000 m relative to the Tarim foreland basin). Such a two-episode uplift history is comparable to the two episodes of rapid cooling events recorded along the eastern margin of the Tibetan Plateau 3 .…”
Section: Discussionmentioning
confidence: 72%
“…The Tarim Block to the north has an Archaean to Proterozoic crystalline basement. Shallow-marine limestone and calcareous shale were deposited for much of the time from the Cambrian until at least B25 Myr, and could be as late as B15 Myr 10,21 . Sequence stratigraphic boundaries and their ages within the study region are based on the fossil record and lateral correlations with type sections of the Tarim basin 22,23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closely nested diversification rate shifts during the Late Miocene to Early Pleistocene (~12-1 Mya) (shifts 4, 5, and 7-15) occurred only in two characteristically Tibetan lineages of polyploidy cyprinids, with one (shifts 7-15) composed entirely of the cleft breast cyprinids in the genus Schizothorax and the other (shifts 4 and 5) the highly specialized schizothoracine fishes except the Schizothorax (clade SCH and SPE, respectively, Figure 3). Although the southern Tibetan Plateau underwent its main stage of fast uplift in the Early Miocene and the elevation probably remained unchanged over the past 15 million years (Harris, 2006;Spicer et al, 2003), further significant uplifts (with possible intervening deformation) of the east and north of Tibet took place within recent 15 million years (Lu et al, 2004;Ritts et al, 2008). Geological evidence suggested that rapid uplift might take place in Eastern Tibet since about 15 Mya because an cessation of rapid Pacific trench migration during the Early to Middle Miocene (~20-15 Mya) probably contributed to the onset of rapid surface uplift and crustal thickening in Eastern Tibet (Royden et al, 2008).…”
Section: Patterns Of Diversifications Of the Schizothoracinsmentioning
confidence: 99%
“…However, this requires an accelerated slip rate between 25 and 17 Ma of 300 km offset (c. 40 mm a À1 ). Therefore a two-stage evolution in fault kinematics has been suggested with fast slip and extrusion during the Late Oligocene-Early Miocene changing to slow slip and crustal thickening up to the present (Yue & Liou 1999;Yue et al 2003;Ritts et al 2008). …”
Section: Geological Offsets and Slip Ratesmentioning
confidence: 99%